Effect of initial biomass on cellulose hydrolysis by leachate communities. (8th June 2009) - Jensen, P.D.; Hardin, M.T.; Clarke, W.P.
Batch anaerobic digestions were performed in 160 ml serum vials, cellulose (1% wt) was the sole added carbon source. All reactors were inoculated with a 10% (v/v) leachate inoculum. The concentration of micro-organisms in the leachate inoculums was increased using centrifugation to investigate the effect of initial biomass on hydrolysis performance. The hydrolysis rate constant for digestions with the highest initial biomass was 0.14 day−1 compared to 0.06 day−1 in digestions with the lowest initial biomass. The results of this study indicate that hydrolysis performance is related to initial biomass concentrations. This is an ongoing project.